High Resolution Intravital Imaging of the Renal Immune Response to Injury and Infection in Mice - Sedin, John; Giraud, Antoine; Steiner, Svava E.; Ahl, David; Persson, A. Erik G.; Melican, Keira; Richter-Dahlfors, Agneta; Phillipson, Mia (Frontiers in Immunology, 2019)
Urinary tract infections caused by uropathogenic Escherichia coli are one of the most common infections, and can lead to sepsis or end-stage renal failure. To be able study the pathology of kidney infection longitudinally, we developed an experimental set up that enables long-term studies of immune cell behavior in situ in the challenged as well as unchallenged kidney of anesthetized mice. Using highly controlled vacuum to stabilize the kidney, the superficial renal cortex was continuously visualized with minimal disruption of the local microenvironment. No visible changes in blood flow or neutrophils, monocytes and macrophages numbers were observed over several hours of visualizing the unchallenged kidney, indicating a stable tissue preparation without apparent tissue damage. Applying this set up to monocyte/macrophage (CX3CR1GFP/+) reporter mice, we observed an extensive network of stellate-shaped CX3CR1 positive cells (previously identified as renal mononuclear phagocytes) as well as intravascular neutrophils that crawl within the microvasculature of the healthy kidney. The extended dendrites of the CX3CR1 positive cells were found to bridge multiple capillaries and tubules and were in constant motion. Light induced sterile tissue injury resulted in rapid neutrophil recruitment to the site of injury. Microinfusion of uropathogenic Escherichia coli into a single nephron induced a rapid and massive recruitment of neutrophils to the site of infection, in addition to active bacterial clearance by neutrophils. In contrast, the kidney resident mononuclear phagocytes did not increase in numbers or migrate towards the site of injury or infection. In conclusion, this model allows for longitudinal imaging of host responses to localized kidney challenges and highlights the extensive network of renal phagocytes and their behavior in vivo in health and disease.